Pemodelan Kanal 38 GHZ Untuk Komunikasi 5G Menggunakan Nyusim - Irfan Alwandi Pohan; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The development of fifth-generation network telecommunications technology (5G) in Indonesia can make commercial, medical, academic, and governmental services more efficient and faster in the field of communication so that 5G technology is needed for the future. The 5G telecommunications technology can be optimally applied in Indonesia in 2020 if the parameters are designed following Indonesia's 5G channel. Channel Modeling 38 GHz for 5G communication using NYUSIM (New York University Simulator) using Matlab-based SSCM (Software Statistical Channel Modeling) data. This research was conducted in Pekanbaru City sub-District for the urban microcell (UMi) scenario, the resulting value was in the form of Pathloss value (125.5 dB), Power Receive (-95.5 dBm), AOA (Angle of Arrival) angle of arrival (from receiver to transmitter) displays the angle received is ± 180 degree, while the AOD (Angle of Departure) departure angle (from the transmitter to the receiver) shows the angle of departure is ± 270 degree, and the Omnidirectional Power Delay Profile (PDP) value is 750 ns with standard deviation is 12.3 ns. The results displayed are a reference source and make future predictions for researchers for installer, planners and commercial communication with 5G. Keywords : NYUSIM, Power Delay Profile, Pathloss